The Relationship between the Thai Army and the Chinese Army in the Time of the National Council for Peace and Order (NCPO) - Kongjieng, Thanaphon (The Journal of Development Administration Research, 2020)
This research aimed to study 1) the relationship between the Thai Army and the Chinese Army during the era of the National Council for Peace and Order (NCPO). 2) the scope of the use of political power of the Thai Army and the Chinese Army. 3) the problems and obstacles in exercising the political power of the Thai Army Forces and the Chinese Army Forces and 4) to propose ways to develop relations and cooperation in the social development, economic and politics of the Thai government and the Chinese government. This is qualitative research; the tool is document research and in-depth interviews, from the key informants are people or agencies related to foreign affairs, society, economy and politics of Thai and Chinese military consisting of 3 government sectors, 3 academics and 1 private sector. The results of research found that 1) the relationship between the Thai army and the Chinese army has developed to a more stable level. Which is a consequence of the past and has been connected to the present. 2) the Thai Army and the Chinese Army have an appropriate military strategy to protect national interests. In implementing security policies in line with regional and global security environments that change according to the global society context, through bilateral and multilateral cooperation with ASEAN. 3) military government during the era of the National Council for Peace and Order (NCPO), turned to rely on China Because it is not accepted the United States and Western countries. Therefore, the relationship began with the acceptance of Thailand to have a military government. Became a channel that leads to close contact and good cooperation in the later stages between the Thai military and the Chinese government. 4) the guidelines for the development of relations found that although Thailand and China have a special relationship with intimacy. As if they were relatives in the same family However Every country would naturally see their own interests. And the exact thing is the relationship between Thailand and China must be based on foreign policy that is able to respond to the national interests of Thailand. Including the strengthening of mutual trust for cooperation and development in all areas of both countries.